Liquid Fertilizer Solution Stirring Tool Using Arduino Uno Microcontroller - Muhammadin Hamid; Aritonang, Endah Sharon; Cholillah, Putri; Afdila, Ryandika; Wijoyo, Hadi (Journal of Technomaterial Physics, 2025)
Automatic fertilizer mixing is required to minimize fertilizer and water mixing time because manual liquid mixing takes a long time. The fertilizer used is liquid, often known as effective microorganisms 4 (EM4) solution. To perfect the stirrer, which is still rotated manually, the DC motor provides speed control for the automatic liquid fertilizer mixer. The speed can be reduced by utilizing the Arduino Uno microcontroller so that the motor rotates according to the required speed. The main mechanical components consist of a DC motor, Arduino Uno as a microcontroller, a power supply as a source of electric current, and a container for mixing liquid fertilizer. The infrared (IR) sensor achieved high accuracy in measuring mixer rotational speed for EM4 fertilizer, with percentage errors ranging from 0.2% to 1.8% compared to tachometer readings. However, when applied to green fertilizer, the error rates varied widely, from 0.03% up to 28.05%, indicating significant fluctuations. These results highlight that the IR sensor is quantitatively reliable for EM4 fertilizer applications but requires further calibration to ensure consistent performance with other fertilizer types